Predicting the General Physical Fitness Level through Series of Field Tests among Students with Hearing-Impaired in Klang Valley, Malaysia - Meera Abdullah, Nagoor; Tumijan, Wahidah; Parnabas, Vincent; Omar Fauzee, Mohd Soffian; Nazarudin, Mohamad Nizam; Sumartiningsih, Sri (Media Ilmu Keolahragaan Indonesia, 2012)
Children with disabilities such as hearing impairment normally indicate lower physical fitness than their hearing peers and place them at risk for secondary health problems. About 70% of hearing impaired children were not involve in physical activity and have lower physical fitness levels than students without disabilities . Deafness or hearing impairment is referred as sensory disability with hearing loss exceeding than 55dB. Almost children indicated hearing impairment have demonstrated lower physical fitness levels than their hearing peers. Hearing impaired children need a healthy lifestyles behaviour, which the general consensus in this group has demonstrated lower physical fitness levels than their hearing peers. Therefore, the reasons why populations of this group have showed lower physical fitness still have limited of studies. The objective of the study is to determine the physical fitness levels and between genders among hearing-impaired students on selected fitness components. The demographic data consists of the age group, gender, height, weight, BMI and also selected fitness components was been compiled. The convenient sampling was used to determine the hearing-impaired students. The total sample of 61 hearing impaired students (male =49; female=12) was selected from a special school for the deaf. Demographic data was collected, and series of selected fitness test batteries was carried out such as 10m shuttle run test, handgrip strength test, vertical jump test, standing broad jump test, sit and reach test, sit up test and also 1600m run test. Descriptive statistics was used to determine the level of fitness among the students. ÃÂ Results show that the male students performed better than the female students in all the test batteries. The most important thing was both students can perform all the fitness tests and also the test can be used to determine the level of fitness with comparison to their hearing peers. The finding of the study may enhance the identification of fitness level of hearing-impaired students which may improve the health outcomes in them.